STUDI KELAYAKAN USAHA TANI TEBU SISTEM BIBIT AWAL DIKECAMATAN PITU KABUPATEN NGAWI - Yunus, Zahrul; Prasetyowati, Kusriani; Mahananto, Mahananto; Suswandi, Suswadi (JURNAL ILMIAH AGRINECA, 2017)
Viewsofnaturalresources thatalargeanddiverse, theagricultural sectorhas apromosingfuture if can continue to be developed, the majority of  the Indonesia population livelihood in agriculture.Todaytherearemanysomepeoplewho  don’t understandtheexact methodof calculationof thecostof doingbusinessofagriculture.Farmingisn’tonlythecostbutalsotake intoaccountthefeasibility.Indonesiaiscountrythathas thepotensialtodevelopsugarcaneearly seedsystemproduction.Inthiscasebecausethenaturalresourceareownedandcanbeusedas aningredientsugarproduction.theresearch aimstodeterminethecost,revenue,income,and fesaybility  of farming  the sugarcane early seed system. The results of feasibility  studies sugarcaneearly seed systemdistrictNgawi. Basicmethodusedthestudywas descriptive.ResearchlocationsindistrictofPitudistrict Ngawi,becausethatlocationisthelargestproducerof sugarcaneinngawi district.Datausedin thisresearcharesecondaryandprimarydata.To  determinethecost  offarming  byadding variablecostandfixedcost,tofindrevenuebymultiplyingthetotalharvestandtotal cost, determinethefeasibilityoffarmingwithcalculations BEP,R/C,andµ/C. Resultsfeasibilitystudiessugarcaneindistrictof PitudistrictNgawi thatistotal costs Rp.80.908.806,00; revenueRp.115.425.000,00;incomeRp.34.516.193,9.Sugarcaneearly seed systeminditrictof PitudistrictNgawifeasibilitytobedevelopedbecauserevenue (Rp.115.425.000,00)>BEPrevenue(Rp.8.564.598,51),production (2.308,5kw)>BEP production  (689,92kw)price (50.000/kw)BEPprice (35.048,21), R/C (1,42)≥1, µ/C (35,70%) >prevailing wage rate bank interest 12% revenue (Rp. 34.516.193,9) >land lease Rp. 14.637.679,7)labourproductivity(Rp.620.064,46)>prevailingwage rate(70.000).